Feasibility of green commercial vertical system for climbing food plant in urban area - Mokhtar Baharudin, Muhammad Shafiq; Ibrahim, Rahinah; Abdan, Khalina; Rashidi, Ali (Universiti Putra Malaysia Press, 2018)
Urban development and overpopulation have created a serious issue towards food security in the urban area. One of the potential solutions to solve this problem is by bringing food production nearer to the cities. In the past decade, vertical farming has caught our attention as an innovative system to produce food in a high amount with little land space. However, the existing systems are only limited to a certain type of crops. The main purpose of this study is to evaluate the potential vertical farming systems for cultivating the climbing food plants using hydrophobic green material. This is a review article presenting selected literature investigating vertical farming capability, natural fiber-based hydrophobic green material, and potential manufacturing processes of hydrophobic green materials. The results include determination components on the vertical farming systems for climbing food plant, potential natural fiber based on the hydrophobic green material preparation, and potential mass manufacturing of green materials to support vertical farming concept in urban cities. This study contributes in varying crops when developing urban farming by using the future vertical farming systems.